Smart appointment organizer for mobile application / Mohd Syafiq Adam - Adam, Mohd Syafiq (2009)
People use different methods in reminding themselves of the appointments they have through out the day. With the current advancement today, the use of personal diaries is almost obsolete. Therefore, we seek better ways in organizing our busy schedule in the most effective ways possible. This project aims to provide a state-of-the-art prototype of smart appointment organizer in managing and organizing appointment by utilizing mobile technology. Users will not only be reminded of the appointments made but also they can find the shortest path to the appointments' destinations within Universiti Teknologi Mara (UiTM). The development of this project is based on a framework of 5 main stages: planning, analysis, design, implementation and testing. Each stage takes into account the overall outcome of this prototype. The main component of this prototype is the use of Dijkstra algorithm to compute the shortest path from source of appointment to the 6 points of destinations within UiTM Shah Alam. This prototype is dynamic in its development as it can be enhanced to a better version to serve different types of users. Therefore, this project is set out to create a time-saving application for UiTM population in managing their appointment plans in a more accurate and orderly manner. In creating this application, NetBeans IDE 6.5and Java Micro Edition (Java ME) are used. This application can be installing into the mobile phone.